Strategi Guru PAI dalam Mengelola Kemampuan Critical Thinking Siswa untuk Menghadapi Banjir Informasi dan Hoaks di SMK Plus Nurul Hakim Kediri - Muhamad Sakaki; Muh. Zaki; Abdul Malik (MANAZHIM, 2023)
This study aims to determine the strategy of PAI teachers in managing students' HOTS-based critical thinking skills to deal with a flood of information and hoaxes at SMK Plus Nurul Hakim Kediri. This study uses a qualitative approach with a descriptive type of research. This research was conducted at SMK Plus Nurul Hakim Kediri for two months, the subjects of this study were PAI teachers at SMK Plus Nurul Hakim Kediri, research informants were school principals, teachers and students. Data collection techniques used in this study were observation, unstructured interviews and documentation. To analyze data with three steps: condensing data, presenting data, and drawing conclusions. The results of the study show that (1) PAI teachers can implement HOTS-based critical thinking in the form of teachers participating in Subject Teacher Deliberation training, compiling HOTS-based curriculum 13 learning tools, preparing students' souls before learning, training students' critical power, training students' metacognitive skills, training reflective thinking students, train students' psychomotor domains, PAI teachers are admired and emulated, analyze appropriate and accurate information and activate correct thinking. (2) The PAI teacher's strategy in managing HOTS-based students' critical thinking to deal with a flood of information and hoaxes is: problem-based learning strategies, creative and innovative learning strategies, contextual teaching learning strategies and inquiry strategies. (3) The results of the implementation of the learning process carried out to manage HOTS-based students' critical thinking abilities to deal with a flood of information and hoaxes are managing critical thinking power so that students are able to choose valid information, are able to train kinesthetic compliance, increase student activity, teacher strategies in diverse learning, and the achievement of learning objectives.